Applying Panel Dynamic OLS and Panel VECM to Estimate the Relationship between Public Investment, Private Investment and Economic Growth in Developing Asian Countries - Canh, Nguyen Thi; Liem, Nguyen Thanh (Global Journal of Social Sciences Studies, 2018)
This study aims to investigate the link between public investment, private sector investment and GDP based on data from 18 Asian developing countries over a 21-year period (1995-2015). We employ Panel Dynamic OLS and Panel VECM to estimate the long-run relationship among the concerned variables. Our findings suggest that there are differences in the relationship between types of investment in each group of countries, and the short-run link between public investment and private investment is less positive in ASEAN countries compared to their non-ASEAN peers. With regard to the long-run relationship, it is clear that the investment from both government and public-private partnership exerts positive impact on private investment, so there is a long-run crowding-in effect of public investment, which supports the growth in private investment. With regard to the impact of types of investment on GDP, it is found that in the short run all three types of investment in ASEAN countries do not perform as positively as in the case of non-ASEAN countries. However at least in the long run, all three types of investment have favorable impact on GDP for both ASEAN and non-ASEAN countries. Based on this result, we suggest some policy implications for ASEAN developing countries.